The evolutionary origin of the need to sleep: an inevitable consequence of synaptic neurotransmission? - Cantor, Robert S. (Frontiers in Synaptic Neuroscience, 2015)
It is proposed that the evolutionary origin of the need to sleep is the removal of neurotransmitters (NTs) that escape reuptake and accumulate in brain interstitial fluid. Recent work suggests that the activity of ionotropic postsynaptic receptors, rapidly initiated by binding of NTs to extracellular sites, is modulated over longer times by adsorption of these NTs to the lipid bilayers in which the receptors are embedded. This bilayer-mediated mechanism is far less molecularly specific than binding, so bilayer adsorption of NTs that have diffused into synapses for other receptors would modulate their activity as well. Although NTs are recycled by membrane protein reuptake, the process is less than 100% efficient; a fraction escapes the region in which these specific reuptake proteins are localized and eventually diffuses throughout the interstitial fluid. It is estimated that even if only 0.1% of NTs escape reuptake, they would accumulate and adsorb to bilayers in synapses of other receptors sufficiently to affect receptor activity, the harmful consequences of which are avoided by sleep: a period of efficient convective clearance of solutes together with greatly reduced synaptic activity.